Pupil Cycle Time in Household Contacts with Leprosy Patients - Waode Ridhayani; Siti Rukiah Syawal; Batari Todja Umar (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: Household contacts of leprosy patients have a higher risk for infection of leprosy. This study is to determine the change in Pupil Cycle Time (PCT) in household contact with leprosy patients and compare them with normal people who are not in household contact with leprosy patients in Makassar. Methods: It was carried out in Tadjuddin Chalid hospital in Makassar and uses cross-sectional study to 61 subjects for each group. The study subjects are divided into two groups: normal people with household contact with leprosy patients, and normal people without household contact as a control group. PCT examinations were performed to the subjects in both groups using biomicroscope slit lamp and digital stopwatch to determine the value of PCT. Result: The study indicates that the average PCT OD and OS of the group with household contact with leprosy patients are 1119.80 (±169.51) milliseconds and 1123.67 (±189.92) milliseconds respectively. Meanwhile, the PCT OD and OS average of the normal people who are not household contact with leprosy patients are 772.67 (±87.75) milliseconds and 776.85 (±82.87) milliseconds respectively. There is a significant difference of PCT between people with household contact with leprosy and those who are not (p=0.000). The length of household contact with leprosy patients has a significant influence with the PCT (p=0.000). Conclusion: The result proves that the PCT of those in household contact with leprosy patient is longer than that of those without contact. The longer the household contact with leprosy patients, the longer the pupil cycle time. Keywords: Pupil Cycle Time, household contact with leprosy patients, leprosy